(+)- and (−)-Ascomlactone A: a pair of novel dimeric polyketides from a mangrove endophytic fungus Ascomycota sp. SK2YWS-L. Issue 48 (29th November 2017) - Liu, Zhaoming; Chen, Senhua; Qiu, Pei; Tan, Chunbing; Long, Yuhua; Lu, Yongjun; She, Zhigang
Abstract : Two novel enantiomeric polyketide dimers were obtained from a mangrove endophytic fungus Ascomycota sp. with potential α-glucosidase inhibitory activities. Abstract : A pair of novel enantiomeric polyketide dimers, (+)- and (−)-ascomlactone A (1a and1b ), were obtained from a mangrove endophytic fungus Ascomycota sp. SK2YWS-L. The structures were elucidated based on spectroscopic methods, and the absolute configurations were determined by X-ray diffraction and electronic circular dichroism (ECD) calculations. Ascomlactone A possessed an unprecedented polymerization system, which constructed an unusual nine-membered lactone ring between the monomers. A possible biogenetic pathway was proposed. Both1a and1b exhibited significant inhibitory effects against α-glucosidase with IC50 values of 63.7 and 27.9 μM, respectively. A further docking study provided an inside perspective of the action in α-glucosidase.